2023
DOI: 10.1002/adma.202301856
|View full text |Cite
|
Sign up to set email alerts
|

Control of Enzyme Reactivity in Response to Osmotic Pressure Modulation Mimicking Dynamic Assembly of Intracellular Organelles

Abstract: In response to variations in osmotic stress, in particular to hypertonicity associated with biological dysregulations, cells have developed complex mechanisms to release their excess water, thus avoiding their bursting and death. When water is expelled, cells shrink and concentrate their internal bio(macro)molecular content, inducing the formation of membraneless organelles following a liquid–liquid phase separation (LLPS) mechanism. To mimic this intrinsic property of cells, functional thermo‐responsive elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The macromolecular crowding of the intracellular environment could also dramatically modulate the kinetics of biochemical reactions via its influence on the diffusion rate, binding kinetics, and binding strength of biomacromolecules, enzymes, and substrates. To investigate the effect of PEG crowding and PEC encapsulation on enzyme activity, we used CAT as a model enzyme and tested its activity under dilute, crowded, CS/HA encapsulated, and crowding/encapsulation combined conditions (Figures , S9, and S10). When fixing the CS (4.0 g/L) and CAT (0.40 g/L) concentrations, the encapsulation efficiency of catalase decreased from 87 to 29% as the HA concentration increased from 2.0 to 6.0 g/L (Figure a).…”
Section: Resultsmentioning
confidence: 94%
“…The macromolecular crowding of the intracellular environment could also dramatically modulate the kinetics of biochemical reactions via its influence on the diffusion rate, binding kinetics, and binding strength of biomacromolecules, enzymes, and substrates. To investigate the effect of PEG crowding and PEC encapsulation on enzyme activity, we used CAT as a model enzyme and tested its activity under dilute, crowded, CS/HA encapsulated, and crowding/encapsulation combined conditions (Figures , S9, and S10). When fixing the CS (4.0 g/L) and CAT (0.40 g/L) concentrations, the encapsulation efficiency of catalase decreased from 87 to 29% as the HA concentration increased from 2.0 to 6.0 g/L (Figure a).…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, a thick-shell microfluidic system was used to generate a W/O/W double emulsion (Figure ). By using this technique, partially dewetted liposomes were produced, as described in our prior research, , which we use as an artificial cell-like chassis.…”
Section: Resultsmentioning
confidence: 99%
“…By creating cytomimetic protocellular models using water-in-oil-in-water (W/O/W) double emulsions and employing monoblock ELRs and ELR-bioconjugates with PEG and horse radish peroxidase as a model multicomponent enzymatic system, a study model for the kinetics of enzymatic reactions under different osmotic pressures was established. This approach demonstrated that synthetic condensates significantly improved the rate of enzymatic reactions after hypertonic shock ( Schvartzman et al, 2023 ).…”
Section: Elrs As Molecular Models Of Intrinsically Disordered Proteinsmentioning
confidence: 99%